INTEGRATIVE MODEL OF STUDENT AND TEACHER STRESS COPING: THE CORRECTION OF RELATIONS IN EDUCATIONAL, PROFESSIONAL AND PERSONAL INTERACTION - K. G. Kassymova; Z. I. Tyumaseva; G. V. Valeeva; S. V. Lavrinenko; M. R. Arpentieva; B. K. Kenzhaliyev; A. N. Kosherbayeva; A. V. Kosov; O.N. Duvalina (Scientific Journal of Pedagogy and Economics, 2019)
This paper deals with stress, which is a major problem for students and teachers throughout the modern world. Stress is a significant problem in our times and affects both the physical and mental health of people. The main objectives are to ascertain the extent to which stress affects students’ academic success and health and to suggest some techniques and practices cope with stress for students. Stress coping methods are the physiological, behavioral, social and psychological methods to deal with stress (to its prevention and coping). Authors outline and suggest stress management techniques, which are easy to practice for students and teachers even during the lesson and in special activities. In addition to educational and professional stress, it is important to take into account the stresses of personal development and interpersonal relations, which are associated with the “private” or “intimatepersonal” as well as social aspects and layers of relationships.